Anthropometric correlates with performance among world championship triathletes - Ackland, T.; Blanksby, B.; Landers, G.; Smith, D.
Male triathletes who possessed an ectomorphic shape, with a large chest breadth and a high proportional thigh length, were advantaged. However, performance times were negatively influenced by high levels of adiposity (p<0.01) and other measures of body bulk such as hip and thigh girths (p<0.05). Successful female triathletes showed similar characteristics to the males, being advantaged by factors pointing to a linear physique (greater arm span, proportional arm and hand lengths; p<0.05), and with large chest girths (p<0.1). Those athletes with greater adiposity(p<0.01), or greater thigh and hip girths (P<0.05), did not perform as well.